Examining organisational culture change in a UK talent development programme - Feddersen, N. (Liverpool John Moores University, 2020)
Team GB is an international powerhouse in Olympic sports and has become 'much admired around the world for sporting success and the system that exists beneath it' (Grey-Thompson, 2017, p. 4). However, big budgets are levelling the playing field in the Global Sporting Arms Race (cf. De Bosscher, Bingham, Shibli, Van Bottenburg, & Knop, 2008). Instead, De Bosscher et al. (2015) explain that nations should focus on talent development and identification to stay competitive. In contrast, recent inquiries into elite sports in the United Kingdom has unearthed examples of destructive cultures (Grey-Thompson, 2017; Phelps, Kelly, Lancaster, Mehrzad, & Panter, 2017). Rees et al. (2016) indicate that a significant re-think of some of the components of current support programmes and environments is a priority to address cultural issues and improve on talent development. A critical area could be the importance of the environment, including cultural features (e.g. Henriksen, 2010; Martindale, Collins, & Abraham, 2007). Rees et at. (2016) argue that it is vital to provide an evidence-based understanding of identification and development to maintain the success of the prolific sports system. The purpose of this thesis was to examine and develop a talent development programme in the United Kingdom. This thesis followed a qualitative research design integrating Grounded Theory and Action Research into a novel method of doing change processes. The main study in this thesis was a 16-month longitudinal study. The research included one reconnaissance phase (e.g. to understand the context and identify change strategies). It also included four double-cycles of implementing change and reviewing the strategies. The primary data collection strategies were ethnography and ten focus groups. The focus groups were carried out with athletes, coaches, parents, and the national governing body (NGB). Analysis of documents and twenty-six individual interviews with stakeholders supplemented these. Eighteen of these individual interviews were with participants from other governing sports organisations (n=6; GSOs) and NGBs (n=3). The findings in the reconnaissance phase suggested that NGB-1 had a history of conflict. The conflict had alienated the community in the sport from the NGB. The influence of this was that many stakeholders disengaged from NGB-1 and set up volunteer-based talent and elite initiatives. NGB-1 explained that most important aim for change was a change of the prevailing culture. NGB-1 formulated five strategies to do so: (1) internal team development, (2) a talent development programme, (3) coach development, (4) selection policies, and (5) GBR development centres. The following four double-cycles aimed to conceptualise how the change of culture happened and what regulated this process. Three features regulated the process: (i) power relations, (ii) structural conditions, and (iii) coupling. First, power relations were divided into two sub-processes of systemic (e.g. hierarchy, official titles, policies, regulation) and informational (e.g. reward, coercive, referent) power. The influence of the power relations was that a destructive culture emerged when NGB-1 tried to implement the change strategies. Coaches and athletes engaged in antagonistic behaviours (e.g. manipulation, coercion, open critique) towards the NGB. Denial of responsibility and social weighting neutralised the stigma of perpetuating antagonism. These findings suggested ignoring and denying antagonism could lead to a destructive culture. Yet, the support towards NGB-1 increased during double-cycles three and four because NGB-1 managed to mobilise stakeholders within the sport through reward and coercive power. Second, structural conditions included how conditions outside the organisation and inside the organisation influenced the change of culture. The findings suggested that political will had isolated Olympic sports from societal changes prior to the study. However, macrocultural changes to social standards and the power of athletes suggested that the organisational culture was increasingly deficient and required radical changes. This influenced NGB-1 through systemic power. GSO used targets and coercive offers (i.e. an offer the recipient is compelled to follow) to direct the direction of change in the NGB. The data suggested that NGB-1 experienced being torn between efforts to comply with targets and antagonistic behaviours within the sports community. Third, coupling denotes how changes in one organisation call for changes in another. GSOs used their systemic power to dictate appropriate avenues for change. Athletes used their reinforced position by speaking out about aspects that challenged the welfare of athletes and others working in Olympic sports. Last, the process in this thesis produced two working models for doing a change of culture in Olympic sports in the United Kingdom. These are grounded in the findings that suggested that the change of culture was fundamental change to the processes of negotiating the change. The findings also suggested the three features above (i.e. power relations, structural conditions, and coupling) influenced changing the process. The findings might have implications for NGBs and GSOs in the United Kingdom because they provided empirical evidence for the relationship between cultural factors and developing talent development programmes. NGBs could use the working models to guide a change of culture and consider how cultural factors might influence the development of talent programmes. Using these working models could help plan and prepare NGBs for the influence of power relations within their sports community. In addition, organisational practitioners in GSOs can use the findings in this thesis to inform how they interact with other GSOs and NGBs. GSO might consider how their systemic power could influence severe conflict with-in an NGB's sports community if they seek to direct changes.